Axisymmetric inertialess model for the capture of airborne microparticles using an electrospray. - González-Loscertales, Ignacio; Rivero Rodríguez, Josefa; Higuera, F.J.; Hijano-Reyes, Antonio Jesús (Elsevier, 2023)
We theoretically analyze the effectiveness of an electrospray of ultrafine droplets to filter out micron sized particles from a gas stream. To that end, we introduce an axisymmetric configuration where the airborne particles merge with the electrospray. The droplets attach to the particles, charging them, and both droplets and charged particles are eventually driven towards a collector by means of an electric field. The attachment process is described through a set of reaction constants based on calculated collision cross-sections, yielding particles with different charge levels. The problem involves computation of the concentrations of each type of particle, the gas flow, and the electric field due to the applied voltages and the space charge. Preliminary numerical simulations show a filtration efficiency that is above 95% for particles larger than about 2 μm and rapidly declines for smaller particles, though this drop of the efficiency can be postponed to smaller particle sizes by decreasing the ratio of particle to electrospray fluxes or the ratio of the inlet velocity of the particle carrying gas to the velocity induced by electric forces inside the device. Pending an exhaustive numerical exploration of the parameter space of the system, these results also show that the gas flow structure, which is strongly affected by the charged particles, is key for high filtration efficiency.
Keywords: Dinamica de fluidos - Proceso de datos; Gases - Separación; Electrosprays; Charged droplet–particle interaction; Particle removal; Filtration; CFD